FORMATION OF CONSTITUTIONAL LITERACY OF PRIMARY SCHOOL STUDENTS - Jabborova O. M.; Ashurova D.R. (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the issue of formation of constitutional literacy of primary school students.